2010
DOI: 10.1093/humrep/deq120
|View full text |Cite
|
Sign up to set email alerts
|

Soluble HLA-G is an independent factor for the prediction of pregnancy outcome after ART: a German multi-centre study

Abstract: This study provides significant evidence that the morphological scoring system is still the best strategy for the selection of embryos but that sHLA-G might be considered as a second parameter if a choice has to be made between embryos of morphologically equal quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(80 citation statements)
references
References 30 publications
1
74
0
Order By: Relevance
“…Among these, HLA-G was found to be produced by human oocytes and embryos and has been investigated in a clinical setting due to its association with successful pregnancy outcome (52). Anyway, several multicentre trials did not confirm these findings (53)(54)(55) demonstrating that HLA-G does not improve embryo selection compared to standard morphology evaluation. Due to the multifactorial nature of embryo development, the protein profiling focused on other method such as mass @ C I C E d i z i o n i I n t e r n a z i o n a l i spectrometry (MS).…”
Section: Proteomicsmentioning
confidence: 99%
“…Among these, HLA-G was found to be produced by human oocytes and embryos and has been investigated in a clinical setting due to its association with successful pregnancy outcome (52). Anyway, several multicentre trials did not confirm these findings (53)(54)(55) demonstrating that HLA-G does not improve embryo selection compared to standard morphology evaluation. Due to the multifactorial nature of embryo development, the protein profiling focused on other method such as mass @ C I C E d i z i o n i I n t e r n a z i o n a l i spectrometry (MS).…”
Section: Proteomicsmentioning
confidence: 99%
“…HLA-G expression is highly tissue-restricted: besides being expressed in fetal tissues, such as trophoblast cells (Rizzo et al, 2011), HLA-G constitutive expression was found in adult thymic medulla (Mallet et al, 1999), cornea (Le Discorde et al, 2003), pancreatic islets (Cervera et al, 2010) and erythroid and endothelial-cell precursors (Rebmann et al, 2010). However, HLA-G expression can be induced in cancers (Rouas-Freiss et al, 2005), transplantation (Sheshgiri et al, 2010), multiple sclerosis (Wiendl et al, 2005), inflammatory diseases and viral infections (Fainardi et al, 2011).…”
Section: Serum Human Leukocyte Antigen-g and Soluble Interleukin 2 Rementioning
confidence: 99%
“…Human embryonic tissues possess a range of proteins and mechanisms that efficiently counteract and prevent maternal cytotoxic T cell attack and thereby provide protection and immune privilege to the fetus (Clark, 2005;Fändrich, 2002;Mor & Abrahams, 2009;Parhar et al 1989;Petroff & Perchellet, 2010;Rebmann et al, 2010;Rizzo et al, 2011a;Verloes et al, 2011). Knowledge of the immunological tolerance mechanisms taking place at the feto-maternal interface in mouse and rat models have contributed to extend such findings to human cells.…”
Section: Immunological Tolerance At the Fetal-maternal Interfacementioning
confidence: 99%
“…HLA-G expression is also claimed to be associated with embryo implantation, the protection of the allogeneic fetus from the maternal immune system, and placentation (section 3; Rebmann et al, 2010;Rizzo et al, 2011a). HLA-G protein expression was found to be constitutive in hMSC and the level was not modified upon stimulation by allogenic lymphocytes in hMSC-mixed lymphocyte reaction assay (Nasef et al 2007).…”
Section: Hla-g and Lifmentioning
confidence: 99%